The adoption of integrated marketing communication by B40 women in Malaysia: an Islamic perspective - Mokhtar, Aida; Wahid, Norashikin (Kolej Universiti Islam Melaka, 2021)
Women make up almost half of the Malaysian population in 2021. A sizeable number of the women are poor and categorised as the Bottom 40 percent (B40). The focus of the study is on Muslim B40 women who are already entrepreneurs. The purpose of the study was on examining out how these women who have poor education could be trained effectively on using integrated marketing communication (IMC) to promote their businesses. IMC is a promotional strategy that uses advertising, public relations, promotion, direct response, and other marketing communication tools in an integrated manner to meet specified objectives. When used effectively, IMC campaigns can help entrepreneurs increase the sales of their products making it useful for B40 women. A case study examining the ideal components of a module for a proposed IMC training program for Muslim B40 women from the perspective of academicians was conducted. The theory of diffusion of innovation theory was adopted to frame the study. The women were categorised in terms of their rate of adoption of IMC before proposing a module and training program for them. The findings suggested that Islam should be at the core of the module, followed by a session on self-development, entrepreneurship skills, e-commerce skills, and IMC skills. This study is significant as relates to the Malaysian government’s policy of transforming the B40 Malaysian population to become financially independent.